PENGELOLAAN SAMPAH BERBASIS SUMBER DI DESA ADAT SANGEH KECAMATAN ABIANSEMAL KABUPATEN BADUNG BALI - Trisna Dewi, Putu Eka; Karyoto, Karyoto; Gede Swetasoma, Cokorda; Toya, I Nyoman; Susanto, Joko; Pariawan, I Wayan; Sudiarta, I Wayan; Susanto, Roni Eko; Suarka, I Made (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2023)
Sangeh Tourism Village is one of the tourist villages in Badung Regency which has various tourism potentials that can still be developed and optimized. One of the problems of the Tourism Village is related to waste management at tourist attractions. Of course, organic and inorganic waste must be separated so that it is easy to manage again and does not pollute the environment. The Ngurah Rai University Postgraduate conducted PkM in partnership with DTW Sangeh (Taman Mumbul and Alas Nutmeg) which invited the Head of the Sangeh Traditional Village and the Head of the Sangeh Traditional Village to discuss with Community Service participants regarding the problems that exist in the management of the Sangeh Tourism Village. So on this occasion, the Postgraduate Program at Ngurah Rai University, apart from cleaning the environment by sorting waste based on sources, also handed over 2 trash cans that could be used at the Sangeh tourist spot.